Kingdom of the Netherlands-Netherlands : Report on the Observance of Standards and Codes (ROSC) Fiscal Transparency Module. (IMF Staff Country Reports; Country Report, 2006)
The report on the Netherlands on the Observance of Standards and Codes discusses the fiscal transparency module and the Aide-Memoire regarding the fiscal framework. The roles and responsibilities of and within government are, in general, clearly defined and, in many areas, the Netherlands sets best practice standards. The basic principles of the trend-based fiscal framework include the separation of tax receipts and outlays, a stable and well-defined set of expenditure rules, and use of expenditure ceilings to implement policy.